1979
DOI: 10.1002/bjs.1800661119
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative hypoxaemia: Oesophagectomy with gastric replacement

Abstract: Pre- and postoperative arterial blood samples were analysed for oxygen partial pressure (PaO2) and carbon dioxide partial pressure (PaCO2) in a consecutive series of 21 patients subjected to two- or three-stage oesophagectomy for carcinoma of the oesophagus. The forced vital capacity (FVC) was measured at the same time. On the second postoperative day the PaO2 showed a fall to 65 per cent of the preoperative value followed by a gradual recovery to 78 per cent on the tenth postoperative day. After 13 weeks the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
2

Year Published

1982
1982
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 15 publications
(11 reference statements)
0
12
0
2
Order By: Relevance
“…Respiratory efficiency may be further worsened because of the transposition of the stomach into the chest [71]. The rate of respiratory complications after esophago-gastric resection varies between studies, ranging from 8 to 45% [71][72][73].…”
Section: Thoraco-abdominal Surgerymentioning
confidence: 99%
“…Respiratory efficiency may be further worsened because of the transposition of the stomach into the chest [71]. The rate of respiratory complications after esophago-gastric resection varies between studies, ranging from 8 to 45% [71][72][73].…”
Section: Thoraco-abdominal Surgerymentioning
confidence: 99%
“…The results are, however, of minor clinical relevance since the respiratory system has a large functional reserve and it can be predicted that this deterioration does not restrict the patients’ lives. Other studies have presented data reflecting the patient status beyond the immediate postoperative period [4, 5]. In one of these [4] the patients performed 85% of their preoperative capacity 13 weeks postoperatively, and in the other 75% 6 months after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have presented data reflecting the patient status beyond the immediate postoperative period [4, 5]. In one of these [4] the patients performed 85% of their preoperative capacity 13 weeks postoperatively, and in the other 75% 6 months after surgery. Maruyama et al [5] suggested that a muscle-preserving thoracotomy might induce less surgical stress than standard thoracotomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of thoracic esophagectomy and replacement of the resected esophagus with the colon or stomach on the lung and respiratory function have been reported [4][5][6][7], Recently, a method for preserving the right bronchial artery and pulmonary branches of the right vagus nerve to preserve postoperative respiratory function has been tried [8], However, the alterations in respiratory movement of the membranous part of the trachea follow ing removal of the thoracic esophagus, which might have a role as a supporting tissue to the membranous part of the trachea, have not been described previously. The purpose of this study is to assess the alterations of respiratory movement of the membranous part of the trachea follow ing radical operations for esophageal cancer.…”
Section: Introductionmentioning
confidence: 99%